MENGUASAI HAKIKAT MANUSIA INDONESIA, ASUMSI – ASUMSI MENGENAI KEPRIBADIAN KONSELOR DAN KONSELI DALAM KONSELING MODEL KIPAS - Dinayatus sahiyah; Dwi Risma Siti Aisyah; Munzil Khair; Qomariyah Qomariyah; Wahyu Rahman; Rusmiyati Rusmiyati (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
KIPAS counseling model (Intensive, Progressive, Adaptive Counseling toward Structure) as a culturally-based counseling approach rooted in the Indonesian archipelago, relevant to the nation's context. It presents the essence of the Indonesian human being through philosophical perspectives, psychological schools (humanistic, psychoanalytic, behavioristic), and Islamic views. The KIPAS model is positioned as an integrative solution to the challenges of multicultural counseling practices, emphasizing the importance of adaptive counselor personalities and a deep understanding of local culture, as well as counselees who possess inherent potentials that can be developed progressively. This paper asserts that the KIPAS approach is not only culturally responsive but also offers a practical and philosophical framework to enhance the effectiveness of counseling services in Indonesia. The strength of this model lies in the depth of local values that are comprehensively integrated into the counseling process.